2003
DOI: 10.1152/japplphysiol.01155.2002
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training alleviates MCT1 and MCT4 reductions in heart and skeletal muscles of STZ-induced diabetic rats

Abstract: We compared the changes in monocarboxylate transporter 1 (MCT1) and 4 (MCT4) proteins in heart and skeletal muscles in sedentary control and streptozotocin (STZ)-induced diabetic rats (3 wk) and in trained (3 wk) control and STZ-induced diabetic animals. In nondiabetic animals, training increased MCT1 in the plantaris (+51%; P < 0.01) but not in the soleus (+9%) or the heart (+14%). MCT4 was increased in the plantaris (+48%; P < 0.01) but not in the soleus muscles of trained nondiabetic animals. In sedentary d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
38
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 39 publications
7
38
0
1
Order By: Relevance
“…In our earlier study (10), after 1 wk of STZ-induced diabetes, we found that inhibition of lactate oxidation was not accompanied by decreased expression of monocarboxylate transporter-1 (MCT-1) expression or lactate dehydrogenase isoform expression (10); however, after longer periods of STZ-induced diabetes, MCT-1 expression in heart was reduced by ϳ30% (17). It was also shown that MCT-1 expression is reduced in skeletal muscle from obese, nondiabetic Zucker rats (38).…”
Section: Discussionmentioning
confidence: 99%
“…In our earlier study (10), after 1 wk of STZ-induced diabetes, we found that inhibition of lactate oxidation was not accompanied by decreased expression of monocarboxylate transporter-1 (MCT-1) expression or lactate dehydrogenase isoform expression (10); however, after longer periods of STZ-induced diabetes, MCT-1 expression in heart was reduced by ϳ30% (17). It was also shown that MCT-1 expression is reduced in skeletal muscle from obese, nondiabetic Zucker rats (38).…”
Section: Discussionmentioning
confidence: 99%
“…For the analysis of MCT, proteins were isolated from muscles as our laboratory has described previously (4,5,16,36,47,48). MCTs were detected with Western blotting.…”
Section: Mct Proteinsmentioning
confidence: 99%
“…It is now confirmed that there is a family of eight or more MCTs (21). MCT isoforms are expressed in a tissue-specific manner (2, 5, 15-18, 20, 26, 28, 36, 38 -40, 42, 47, 49), and MCTs are also coexpressed within the same tissue (2,4,5,16,29,42,47,49). These latter observations suggest that MCTs may have different roles and/or transport capacities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When glucose disposal is stimulated with insulin, plasma lactate concentration increases and the concentration is positively correlated with the rate of glucose disposal [16]. In STZ induced diabetes (which is a model of type 1 diabetes) resting blood lactate is reported to be elevated [17,18], and STZ induced diabetes in rats has also been found to decrease skeletal muscle lactate transport [17]. Studies have shown that mono-carboxylate transporters (MCT) dependent lactate-H + flux is facilitated by bicarbonate transporters and carbonic anhydrase enzyme in various cells and tissue [19,20].…”
Section: Introductionmentioning
confidence: 99%